National Covenant - Scotland
Facsimile of the National Covenant, an agreement inaugurated by Scots rejecting the attempt by King Charles I and William Laud, Archbishop of Canterbury, to force the Scottish presbyterian system to conform to the English episcopacy.
Facsimile.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Charles -- I, -- King of England, -- 1600-1649.; Laud, William, -- 1573-1645.; Church of England -- History; Church of Scotland -- History; Church and state -- Scotland -- History; Covenanters; Great Britain -- Church history -- 17th century; Scotland -- Church history -- 17th century